2006
DOI: 10.1093/ageing/afj044
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive functioning in spousal caregivers of dementia patients: findings from the prospective MAASBED study

Abstract: The results indicate that screening for cognitive impairment of spousal caregivers may be helpful, because suboptimal cognitive functioning may affect the ability to provide adequate care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
98
5
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(114 citation statements)
references
References 20 publications
7
98
5
4
Order By: Relevance
“…These results are consistent with one previous study (Leipold et al, 2008), but conflict with other studies that found poorer cognitive functioning in spouse caregivers versus married noncaregivers (Caswell et al, 2003; de Vugt et al, 2006; Vitaliano et al, 2009). Our secondary analyses restricted to spouse caregivers and married noncaregivers confirmed the findings in the overall sample that continuous caregivers performed better than noncaregivers.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These results are consistent with one previous study (Leipold et al, 2008), but conflict with other studies that found poorer cognitive functioning in spouse caregivers versus married noncaregivers (Caswell et al, 2003; de Vugt et al, 2006; Vitaliano et al, 2009). Our secondary analyses restricted to spouse caregivers and married noncaregivers confirmed the findings in the overall sample that continuous caregivers performed better than noncaregivers.…”
Section: Discussionsupporting
confidence: 88%
“…For example, longer duration of caregiving was positively associated with increases in cognitive complexity (complex thought) among caregivers to persons with dementia (Leipold et al, 2008). However, some studies found that caregivers to a spouse performed worse (Caswell et al, 2003; de Vugt et al, 2006; Vitaliano et al, 2009), or declined more (Vitaliano et al, 2005) in cognitive functioning than married noncaregivers, but these associations disappeared when adjusted for psychological or metabolic variables (Caswell et al, 2003; Vitaliano et al, 2005; Vitaliano et al, 2009). Other studies found different associations between caregiving and cognitive status depending on the measure used (de Vugt et al, 2006; Lee et al, 2004; Mackenzie, Smith, Hasher, Leach, & Behl, 2007).…”
mentioning
confidence: 99%
“…A comparison group of patients with late-onset dementia (LOD) was selected from a 2-year follow-up cohort study with LOD patients, the MAASBED study (Maastricht Study of Behavior in Dementia) [23], which had a similar design, assessment measures and diagnostic criteria as the NeedYD study. In the MAASBED study, patients with dementia were included irrespective of the diagnostic subtype.…”
Section: Subjectsmentioning
confidence: 99%
“…For example, older adult caregivers have been found to experience greater declines in cognitive functioning over time as compared with matched controls (de Vugt et al, 2006;Vitaliano et al, 2009). Whether some of the biological correlates of chronic stress and aging noted earlier, which may also affect changes in cognitive functioning over time, account for greater risk of cognitive decline in caregivers versus controls is presently unknown.…”
Section: Cognitive and Physical Functioningmentioning
confidence: 99%